Effects of the exercise‐inducible myokine irisin on malignant and non‐malignant breast epithelial cell behavior in vitro. Issue 4 (30th August 2014) - Gannon, Nicholas P.; Vaughan, Roger A.; Garcia‐Smith, Randi; Bisoffi, Marco; Trujillo, Kristina A.
<x xml:space="preserve">Abstract</x> Exercise has been shown to reduce risk and improve prognosis of several types of cancers. Irisin is a myokine linked to exercise and lean body mass, which is thought to favorably alter metabolism systemically, potentially providing benefit for metabolic disease (including cancer). We evaluated the effects of various concentrations of irisin (with and without post‐translational modifications) on malignant and non‐malignant breast epithelial cell number, migration and viability. Irisin significantly decreased cell number, migration and viability in malignant MDA‐MB‐231 cells, without affecting non‐malignant MCF‐10a cells. Moreover, irisin enhanced the cytotoxic effect of doxorubicin (Dox) when added to a wide spectrum of irisin concentrations in the malignant cell type (with simultaneous reduction in Dox uptake), which was not observed in non‐malignant MCF‐10a cells. Additionally, we found that irisin decreases malignant cell viability in part through stimulation of caspase activity leading to apoptotic death. Interestingly, we found that irisin suppresses NFκB activation, an opposite effect of other myokines such as tumor necrosis factor alpha (TNF‐α). Our observations suggest that irisin may offer therapeutic benefits for breast cancer prevention and treatment possibly through an anti‐inflammatory response, induction of apoptotic cell death, or through enhanced tumor sensitivity to common antineoplastic agents such as Dox.